Private Equity and Large-scale Investment in Healthcare Delivery Systems: A Scoping Review - James Kumar Pallivathukkal; Prateek Agarwal; Sambath Prasannakumar Sasikala; Mehala Devi Nagarajan (Journal of Evidence-Based Medical Research, 2026)
Background: External institutional capital increasingly shapes healthcare delivery, yet evidence is fragmented across sectors, investment structures and outcomes. Objectives: To map the extent, characteristics, findings and policy implications of research on private equity (PE) and other large-scale investment in care-delivery organisations. Methods: Following JBI and PRISMA-ScR guidance, PubMed/MEDLINE, Europe PMC and OpenAlex were searched from 1 January 2000 to 22 August 2026, supplemented by citation and targeted policy searches. Eligible empirical studies, reviews and mapped policy syntheses examined institutional investment that changed ownership, control, financing or operating incentives in a delivery organisation. Evidence was charted by country, sector, investment type, design and outcome; heterogeneous findings were narratively synthesised. Results: Of 1,997 records retrieved, 1,414 remained after deduplication and 117 sources were included. The evidence was 88.0% US-based and 95.7% PE-related; 47.9% appeared in 2025–2026. Physician/specialty practices (42.7%) and hospitals (22.2%) predominated. Comparative studies most consistently associated acquisition or affiliation with higher prices, allowed amounts or spending. Quality effects were heterogeneous, with adverse signals in hospital safety and mortality, nursing-home staffing and outcomes, hospice care intensity and experience, alongside neutral findings in some settings. Reported mechanisms included roll-up concentration, price and volume strategies, staffing or service-line changes, sale-leasebacks and higher clinician turnover. Conclusions: Binary ownership labels obscure the pathways through which capital affects care. Oversight should link beneficial ownership and transaction finance to longitudinal workforce, service, quality, access and solvency data across acquisition, ownership and exit.